2014
DOI: 10.3233/jad-140507
|View full text |Cite
|
Sign up to set email alerts
|

Macular Pigment, Visual Function, and Macular Disease among Subjects with Alzheimer's Disease: An Exploratory Study

Abstract: AD patients were observed to exhibit significantly less MP, lower serum concentrations of L and Z, poorer vision, and a higher occurrence of AMD when compared to control subjects. A clinical trial in AD patients designed to investigate the impact of macular carotenoid supplementation with respect to MP, visual function, and cognitive function is merited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 58 publications
(69 reference statements)
6
61
0
Order By: Relevance
“…One possibility is simply protection from the accumulated effects of oxidative and inflammatory stress. Data linking reduced MPOD to dementia [19] and cognitive impairment [23] is consistent with that possibility. Another possibility, more relevant to younger individuals and palliative approaches, is a direct improvement by some type of local interaction with neural cells (the so-called neural efficiency hypothesis; [11,36,21] MPOD) in young healthy subjects would yield behavioral improvements in tasks that are generally mediated by the central nervous system.…”
Section: Introductionmentioning
confidence: 64%
“…One possibility is simply protection from the accumulated effects of oxidative and inflammatory stress. Data linking reduced MPOD to dementia [19] and cognitive impairment [23] is consistent with that possibility. Another possibility, more relevant to younger individuals and palliative approaches, is a direct improvement by some type of local interaction with neural cells (the so-called neural efficiency hypothesis; [11,36,21] MPOD) in young healthy subjects would yield behavioral improvements in tasks that are generally mediated by the central nervous system.…”
Section: Introductionmentioning
confidence: 64%
“…In addition to being protector of vision, clinical research data also suggest that lutein and zeaxanthin may protect against CVDs (Andersen, 2015;Gammone, Riccioni, & D'Orazio, 2015;Shin et al, 2013), oxidative stress (Fiedor & Burda, 2014;Sen & Chakraborty, 2011), neurodegenerative disorders (Calabrese et al, 2010;Feart et al, 2016;Nataraj et al, 2015;Nolan et al, 2014Nolan et al, , 2015, and possibly different types of cancer (Mares-Perlman et al, 2002). Over the years, hen eggs have acquired a bad reputation attributed to the high content of cholesterol mainly in yolks, which led to a serious decline in their consumption.…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%
“…Emerging evidence indicates that higher concentrations of lutein in respect to plasma lipids may moderately decrease the risk of dementia and AD in an elderly community dwellers (Feart et al, 2016). AD patients exhibit significantly less MP and poorer vision [possibly due to lower serum concentrations of lutein and zeaxanthin (Nolan et al, 2014)]. Supplementation with the lutein and zeaxanthin carotenoids benefits patients with AD, in terms of not only clinically meaningful improvements in visual function but also cognitive function is triggered as merited (Nolan et al, 2014(Nolan et al, , 2015Renzi, Dengler, Puente, Miller, & Hammond, 2014).…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%
“…10 Macular pigment (and its constituent carotenoids) may have an important role in age-related macular degeneration (AMD) by reducing oxidative stress via its antioxidant properties as well as limiting the effect of inflammatory mediators in the pathogenesis of this condition. 11 Some studies also have reported that MP may be lower compared to controls among persons with glaucoma, 12 Alzheimer's disease (AD), 13 and diabetes, 14,15 suggesting that MP could be a useful biomarker for these conditions, providing a biologically plausible rationale to investigate whether MP has a role in these pathologies.…”
mentioning
confidence: 99%